Ласточкино гнездо: стихи : переводы с удмуртского / Владимир Романов - Романов Владимир Васильевич (Удмуртия, 2004)
Экземпляры: ф.2 (2005) / Инвентарный номер: 48763 / Цена: / Сис.шифр: 84(2Рос=Удм)6-5 / Авт.знак: Р 69 / ГРНТИ: 17.82.10 / ББК: 84(2Рос=Удм)6-5